Inhibition of UVB-Induced Matrix Metalloproteinase-1 (MMP-1) Expression in Human Skin Fibroblasts Using Lysate of Lactobacillus iners Isolated from the Skin of Korean Women in Their Twenties - 이진성 (The Graduate School, Ajou University, 2024)
The aging process of the skin is intricate, encompassing both intrinsic aging, influenced by internal factors, and extrinsic aging, primarily caused by exposure to UV radiation, leading to photoaging. Photoaging manifests as skin issues like wrinkles and discoloration. The skin microbiome, a diverse community of microorganisms on the skin's surface, plays a crucial role in skin protection and can be influenced by factors such as humidity and pH levels. Probiotics, which are beneficial microorganisms, have been under investigation for their potential to enhance skin health by regulating the skin microbiome. This regulation can be achieved through oral probiotics, impacting the gut–skin axis, or through topical applications that introduce live bacteria to the skin. Probiotics are known to mitigate oxidative stress, suppress inflammation, and maintain the skin's extracellular matrix, ultimately helping to prevent skin aging. However, research on probiotics derived specifically from human skin is limited, and there is currently no established product for preventing photoaging. The mechanism by which probiotics shield the skin microbiome and layers from UV radiation remains unclear. Recent research has identified Lactobacillus in the skin, with reports indicating a decrease in this microorganism with age. In a recent study, scientists isolated the Lactobacillus iners strain KOLBM20 from the skin of individuals in their twenties and confirmed its effectiveness. Genetic sequence analysis revealed that the KOLBM20 strain belongs to the Lactobacillus genus and is closely related to L. iners DSM13335T with 99.20% similarity. Significantly, Lactobacillus iners KOLBM20 displayed anti-wrinkle properties by inhibiting Matrix Metalloproteinase-1 (MMP-1). The investigation demonstrated the inhibitory effect of the KOLBM20 lysate strain on MMP-1 expression. Moreover, the data suggest that the KOLBM20 lysate strain may prevent UVB-induced MMP-1 expression by inhibiting the activation of the ERK, JNK, and p38 signaling pathways induced by UVB. Consequently, the KOLBM20 lysate strain shows potential as a therapeutic agent for preventing and treating skin photoaging. Keywords Lactobacillus; human skin derived probiotics; UVB-induced; MMP-1; 16S rRNA; ERK; JNK; p38
학위논문(박사)--응용생명공학과,2024. 8
Keywords: microbiome; photoaging